Piano sonata no. 13 in E-flat major, op. 27, no. 1, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Iganz, 1794-1870 (editor):::Contributor:::::::::::: (Stuttgart; Eduard Hallberger; Germany, 2023)
Mid-nineteenth century edition of the Piano Sonata no. 13 in E-flat major, op. 27, no. 1, edited by Ignaz Moscheles and published by Eduard Hallberger in Stuttgart as no. 32 of the series "L. v. Beethoven's sämmtliche Sonaten für Pianoforte" in "Hallberger's Pracht-Ausgabe der Classiker."